Digital Transformation in Islamic Educational Management: A Thematic Literature Review of Challenges, Opportunities, and Digital Communication Ethics Based Strategies - Annur Sri Mulyani; Ulfi Wisa Belinda; Utep Ahmad Zulfiqor (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Globalisation places growing pressure on Islamic educational institutions to adopt digital governance systems, yet the transition consistently surfaces structural, ethical, and competency challenges that technology procurement alone cannot resolve. This study conducts a thematic literature review to map the operational challenges, technology adoption opportunities, and management strategies associated with administrative digitalisation in Islamic schools, framed specifically within digital communication ethics. Forty-two documents were retrieved from Google Scholar, SINTA-accredited databases, and DOAJ using the search terms “digitalisasi pendidikan Islam”, “Manajemen Pendidikan Islam”, “etika komunikasi digital”, and “digital transformation Islamic education”; after screening against the inclusion and exclusion criteria, 28 sources were retained for analysis (published 2017–2025). Data were analysed through thematic content analysis involving open coding, theme clustering across the four management functions (planning, organising, actuating, and controlling), and cross-document comparative synthesis. The review identifies that Educational Management Information System (EMIS) adoption demonstrably improves data recording accuracy during planning and organising; however, screen-mediated interaction during actuating and controlling phases is associated in the reviewed literature with weakened supervisory control, cyberbullying, and misinformation circulation. The study proposes that software automation in Islamic schools needs to be balanced with a prophetic digital ethics framework whose core elements are adab-based communication norms, emotional self-regulation, and tabayyun (information verification before sharing). Theoretically, this study extends Islamic educational management theory by recasting data privacy governance as an expression of the Islamic virtue of amanah (trusteeship) in a digital institutional context.